Increasing Community Income through Utilization of Starfruit Waste in Karangsari Village, Blitar City - Aprilia, Lucky; Prayudhi, Luhur Aditya (Agrikan Jurnal Agribisnis Perikanan, 2021)
Utilization of household waste such as eco enzyme and nata de star to diversify star fruit products and then empower farmers to be varied with entrepreneurial strategies and increase the economy of the surrounding community. This activity aims to empower the community through the development of the creative economy of starfruit farmers and increase people's income, especially starfruit farmers in Karangsari Village. The method used in this research is the census method. The results of this study indicate that eco enzyme has many benefits so that it can empower the community. the income in one production process in one production process in the manufacture of eco enzyme is Rp. 303,000 while the manufacture of nata de star is Rp. 785,000 in one production process so that the production of eco enzyme and nata de star is profitable.